Diversity, Abundance, and Threats to Birds in Bhimdatta Municipality, Kanchanpur, Nepal - Bista, Shreyashi; Joshi, Priyanka; Bista, Mahadev (Api Journal of Science, 2024)
The avifaunal survey was conducted in Wards 15, 18, and 19 of Bhimdatta Municipality, Kanchanpur, Nepal, from February 2022 to May 2023 using the Point Count Method. Fixed observation points were established across croplands, rangelands, and urban areas, where birds were recorded within a 50-meter radius during a 10-minute observation period at each point. Bird identification was carried out with the assistance of experts from Bird Conservation Nepal (BCN) and using the revised edition of Birds of Nepal (2022) as a reference. Data were systematically documented, including species, and threats characteristics. This study recorded 29 bird species across 11 orders and 23 families. The order Passeriformes exhibited the highest species richness, with 15 species from 11 families, followed by Galliformes and Coraciiformes, each with four species. Psittaciformes, Accipitriformes, Ciconiiformes, Pelecaniformes, and Strigiformes were the least represented orders, with only one species each. The Black-necked Stork was the sole near-threatened species identified, while the remaining 28 species were classified as least concern according to the IUCN Red List. Threats to avifauna, including habitat loss, urban expansion, and poaching, were identified through field observations and consultations with local stakeholders, emphasising the need for targeted conservation interventions.